Building Sustainability Assessment Methods: current update. Issue 2 (November 2020) - de Fátima Castro, Maria; Andrade, Joana; Bragança, Luís
Abstract: The major reason that promoted the development of systems to support environmental performance assessment of buildings was the effective realisation, in some countries, that they were unable to say how sustainable a building was. Later researchers and government agencies understood that assessment tools are the best method to demonstrate the level of sustainability of all types of constructions. These can improve the education for a sustainable society, because it can promote understanding between the principles of sustainable construction and the user. Within this, several countries have developed their own methods for sustainability assessment adapted to their reality and presenting them as capable of guiding the overall performance of this sector. Most of these methods are based on local rules and legislation, in locally conventional construction technologies, with the default weight of each indicator set according to the actual local socio-cultural, economic and environmental contexts. Through the years, these methods have contributed to the growth of the awareness about criteria and objectives of sustainability, and they have been improved to a more holistic approach. They become a reference to assess the sustainability of buildings in particular and construction in general. This paper proposes to present the evolution of these methods after twenty-five years, comparing and critical analysing the most recognised ones. It will expose the results of comparation, regarding criteria, weights and final scores, and presented the new path these methods are now tracing. A new trend for method to support design rather than certifying an erected building is also presented. In conclusions it will be discussed the pros and cons of the appearance of them and their improvements.